2009
DOI: 10.1208/s12249-009-9296-0
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Dacarbazine-loaded Cubosomes—Part II: Influence of Process Parameters

Abstract: Abstract. The purpose of this study is to investigate the combined influence of process parameters (independent variables) such as homogenization speed (X 1 ), duration (X 2 ), and temperature (X 3 ) during the preparation of dacarbazine-loaded cubosomes. Box-Behnken design was used to rationalize the influence of these three factors on two responses, namely particle size (Y 1 ) and encapsulation efficiency (Y 2 ). Independent and dependent variables were analyzed with multiple regressions to establish a fullm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The method of preparation of DTIC-loaded cubosomes was adapted from previous work of Esposito et al (17)(18)(19). Briefly, for each sample, a volume of 15 ml chloroform was used to completely dissolve 500 mg GMO and 75 mg F127.…”
Section: Preparation Of Dacarbazine-loaded Cubosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of preparation of DTIC-loaded cubosomes was adapted from previous work of Esposito et al (17)(18)(19). Briefly, for each sample, a volume of 15 ml chloroform was used to completely dissolve 500 mg GMO and 75 mg F127.…”
Section: Preparation Of Dacarbazine-loaded Cubosomesmentioning
confidence: 99%
“…Previous studies reported that even lipophilic drugs were rapidly released from cubosomes after ultrafiltration (26). However, sample #2 (F2+) and control #2 (F2−) were prepared using the method resulting from the process parameters study (19). In this case, using 500 mg of GMO, 75 mg of F127, and 10 mg of DTIC, minimal particle size was achieved with approximately 24,000 rpm of homogenization speed, 5.4 min of duration, at 76°C±2°C temperature.…”
Section: Dacarbazine-loaded Cubosome Morphology and Drug Loadingmentioning
confidence: 99%
“…23,24 The authors have recently combined the concept of design of experiments with nanoformulation. 25,26 In this study, an easy and effective method of preparing spray-dried NCs without using the classical rotary evaporator was developed. The influence of three different formulation variables was studied using a Box-Behnken design to optimize spray-dried NCs.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained t , which indicates the main effect of the independent variables and interactions on the Y 1 value, is compared with a tabulated critical t-value (the absolute value of t Critical = 2.57) at p < 0.05, which is determined at α = 0.05 for the residual degrees of freedom (df), where df = 5 [39]; both t Critical values are shown in the two vertical lines in Figure 1B. The factors whose length passed the vertical line indicate significance on the response value [40]. The positive sign of the coefficient shows a positive effect on the size of the responses, while the negative signs indicate a negative effect.…”
Section: Resultsmentioning
confidence: 99%